Assessment of Pesticide Contamination of Groundwater from Titu-Sarata Plain, Romania - Crinela Dumitrescu; Claudia Stihi; Diana Costinel; Elisabeta Irina Geana; Corina Teodora Ciucure; Diana Ionela Popescu (Stegarus); Danut Tanislav; Petre Bretcan (Applied Sciences)
In Romania, groundwater is an important source of drinking water, especially in rural areas. This study investigated the concentrations of organophosphorus, carbamate, and triazine pesticides (OPs) along with organochlorine pesticides (OCPs) in groundwater samples collected from the Titu-Sarata Plain. Sensitive analytical techniques were employed, including Ultrahigh-Performance Liquid Chromatography coupled with Q Exactive™ HF Hybrid Quadrupole-Orbitrap™ Mass Spectrometry (UHPLC-Orbitrap-MS/MS) and Gas Chromatography coupled with an electron capture detector (GC-ECD). Environmental and human health risks were assessed in the case of pesticides that exceeded the maximum allowed concentration. The environmental risk assessment (ERA) revealed significant risks associated with Phosdrin, Phorate, and pp’DDE. Additionally, particular concerns arose from the presence of Aldrin and Dieldrin, which pose a high carcinogenic risk, especially through groundwater consumption in agricultural areas. The results of this research highlight the need for the implementation of a continuous quality monitoring program for groundwater in the agricultural regions that were studied.